Vermittlungshorizonte. Erziehungswissenschaftliche Reflexionen über hochschul- und wissenschaftsdidaktische Herausforderungen - Freitag, Christine (Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Der Briefroman als Medium weiblicher Kritik in der Aufklärung – Einblicke in Caroline Rudolphis »Gemälde weiblicher Erziehung« - Vochatzer, Stefanie (»Debattieren, Opponieren, Protestieren – Interdisziplinäre Perspektiven auf sprachliche Praktiken des Widersprechens«)

Efficient Shape Formation by 3D Hybrid Programmable Matter: An Algorithm for Low Diameter Intermediate Structures. SAND 2024: 15:1-15:20 - Scheideler, Christian; Hinnenthal , Kristian; Liedtke, David Jan

Polylogarithmic Time Algorithms for Shortest Path Forests in Programmable Matter. - Scheideler, Christian; Padalkin, Andreas

Universal Coating by 3D Hybrid Programmable Matter. - Scheideler, Christian; Kostitsyna, Irina; Liedtke, David Jan

The structural power of reconfigurable circuits in the amoebot model. - Scheideler, Christian; Padalkin, Andreas; Warner, Daniel (The structural power of reconfigurable circuits in the amoebot model. Nat. Comput. 23(4): 603-625 (2024))

Routing schemes for hybrid communication networks. - Scheideler, Christian; Coy, Sam; Czumaj, Arthur; Schneider, Philipp; Werthmann, Julian (Routing schemes for hybrid communication networks. Theor. Comput. Sci. 985: 114352 (2024))

Invited Paper: Blockchains made Lightweight: A Median Rule for State Machine Replication. - Scheideler, Christian; Dou, Jinfeng

Reconfiguration and Locomotion with Joint Movements in the Amoebot Model. - Scheideler, Christian; Padalkin, Andreas; Kumar , Manish

„Und ich sag mal, Theorie und Praxis ist zweierlei” – Wie können Praxisphasen Lehramtsstudierende auf zukünftige Anforderungen vorbereiten? - Vernholz, Mats; Jonas-Ahrend, Gabriela

Sodium 4-styrenesulfonyl(trifluoromethanesulfonyl)imide-based single-ion conducting polymer electrolyte incorporating molecular transporters for quasi-solid-state sodium batteries - Wunder, Clemens; Lai, Thanh-Loan; Šić, Edina; Gutmann, Torsten; Vito, Eric; Buntkowsky, Gerd; Zarrabeitia, Maider; Passerini, Stefano (Journal of Materials Chemistry A)
Sodium batteries are an attractive alternative for future energy storage as they can be produced with abundant and low-cost materials. Nonetheless, sodium-ion batteries (SIBs) are often composed of flammable and volatile carbonate-based liquid electrolytes. Polymer electrolytes have attracted significant attention as safer alternatives. Among polymer electrolytes, single-ion conductive polymer electrolytes (SIPEs) are considered particularly interesting because they can suppress dendrite growth, enabling high-performance (quasi)-solid-state sodium–(metal) batteries. In this work, a self-standing, flexible, quasi-solid-state SIPE is investigated, which is composed of sodium 4-styrene sulfonyl (trifluoromethanesulfonyl) imide (NaSTFSI), pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) and pentaerythritol tetraacrylate (PET4A) blended with poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP). The SIPE membrane, including 50 wt% of molecular transporter, exhibits ionic conductivity of 1.4 × 10−5 S cm−1 and 1.3 × 10−4 S cm−1 at 20 °C and 90 °C, respectively, thermal stability up to 280 °C, electrochemical stability window up to 4.5 V vs. Na/Na+, and Na plating/stripping reversibility in symmetric Na‖Na cells. The manufactured SIPE implemented in Prussian White (PW)‖Na cells enables the delivery of 147 mA h g−1 of PW at 15 mA g−1 with a Coulombic efficiency of over 99%, which is comparable with the PW‖Na cells using liquid carbonate electrolyte, confirming the suitability of the designed SIPE for sodium–(metal) batteries.

Novel Heterogeneous Pd Catalysts for Cross-Coupling Reactions in Biocompatible Media: Structural Insights from Solid-State NMR Techniques - Wissel, Till; Rösler, Lorenz; Brodrecht, Martin; Höfler, Mark V.; Herr, Kevin; Oliveira Jr., Marcos; Klimavicius, Vytautas; Ebert, Martin; Breitzke, Hergen; Hoffmann, Markus; Buntkowsky, Gerd; Gutmann, Torsten (ChemCatChem)
Abstract Novel SBA-15-supported heterogeneous catalysts are synthesized and applied in the Mizoroki?Heck and the Suzuki?Miyaura cross-coupling reactions in green solvents like PEG or water. The structural properties of the products after each synthesis step are monitored by different analytics. The amount of amine/carboxyl groups and vanillin/histidine methyl ester and thermal stability are determined by TGA and elemental analysis, while ICP-OES delivered the amount of palladium of the catalysts. The morphology is investigated by SEM and XPS and confirms the presence of coordinated palladium in the zero-oxidation state. Gas adsorption analysis is conducted, which indicates the presence of palladium clusters in one of the two catalysts, which is underlined by BSE images combined with EDX. A detailed 13C ssNMR and DNP-enhanced 15N ssNMR spectral analysis is presented, which provides ultimate proof of the successful syntheses of the catalysts. The coordination of the palladium onto the carrier material is shown by combining the NMR spectral results with the results of the other analytics. First catalytic tests show for the Mizoroki?Heck reaction yields up to nearly 100% and for the Suzuki-Miyaura up to 88% in the presence of PEG and water, respectively.
Keywords: SBA-15; Heterogeneous catalyst; Pd cross-coupling; Polyethylene glycol; Solid-state DNP NMR

Towards Routine 7Li In Situ Solid-State NMR Studies of Electrochemical Processes in Li\textbarLiPF6\textbarLFP Cells - Šić, Edina; Fredericks, Dominion; Pecher, Oliver; Wegner, Sebastian; Breitzke, Hergen; Singh, Vickram; Buntkowsky, Gerd; Gutmann, Torsten (Applied Magnetic Resonance)
In this study, electrochemical processes in a Li{|}LiPF6{|}LFP cell have been explored applying advanced solid-state NMR technologies. In situ solid-state NMR allows to monitor structural changes in local environments in commercially available cell components during galvanostatic cycling. In collaboration with Dragonfly Energy, ePROBE GmbH and Bruker BioSpin GmbH & Co. KG, we have demonstrated an experimental procedure for routine application of in situ solid-state NMR for battery research. This points out the high potential of this approach for use in the energy storage industry.

At the limits of bisphosphonio-substituted stannylenes - Nasemann, Sina; Franz, Roman; Kargin, Denis; Bruhn, Clemens; Kelemen, Zsolt; Gutmann, Torsten; Pietschnig, Rudolf (Chemistry - An Asian Journal)
Abstract Donor stabilization of Sn(II) and Pb(II) halides with 1,1?-ferrocenylene bridged bisphosphanes has been explored for Fe(C5H4P(C6H5)2)2 (dppf), and Fe(C5H4PH(C4H9))2. These bisphosphanes are reacted with SnBr2 and PbCl2 with and without additional Lewis acid (AlCl3) forming acyclic and cyclic donor adducts from which the latter represent bisphosphoniotetrylenes. Since dynamic exchange in solution is observed, characterization includes solution and solid-state NMR in addition to SC-XRD, amended by DFT calculations.
Keywords: ferrocene; lead; phosphorus; tetrylene; tin

A solid xantphos macroligand based on porous organic polymers for the catalytic hydrogenation of CO2 - Nisters, Arne; Gutmann, Torsten; Kim, Sun-Myung; Hofmann, Jan Philipp; Rose, Marcus (RSC Sustainability)
Porous organic polymers enable a novel approach to incorporate xantphos into a solid macroligand. Immobilizing a ruthenium complex on the xantphos framework results in an excellent catalyst for the hydrogenation of CO2 to formic acid. Recycling experiments indicate a minor partial degradation of the heterogenous catalyst after a certain induction period, which is referred to its structural changes.

Highly productive V/Zn-SiO2 catalysts for the selective oxidation of methane - Kunkel, Benny; Seeburg, Dominik; Kabelitz, Anke; Witte, Steffen; Gutmann, Torsten; Breitzke, Hergen; Buntkowsky, Gerd; Buzanich, Ana Guilherme; Wohlrab, Sebastian (Catalysis Today)
The production of formaldehyde on industrial scale requires huge amounts of energy due to the involvement of reforming processes in combination with the demand in the megaton scale. Hence, a direct route for the transformation of (bio)methane to formaldehyde would decrease costs and puts less pressure on the environment. Herein, we report on the use of zinc modified silicas as possible support materials for vanadium catalysts and the resulting consequences for the performance in the selective oxidation of methane to formaldehyde. After optimization of the Zn content and reaction conditions, a remarkably high space-time yield of 12.4 kgCH2O·kgcat−1·h−1 was achieved. As a result of the extensive characterization by means of UV–vis, Raman, XANES and NMR spectroscopy it was found that vanadium is in the vicinity of highly dispersed zinc atoms which promote the formation of active vanadium species as supposed by theoretical calculations. This work presents a further step of catalyst development towards direct industrial methane conversion which may help to overcome current limitations in the future.
Keywords: Formaldehyde; Local coordination; SBA-15; Vanadium oxo species; XANES; Zinc doped silica

Mechanochemical Cyclotrimerization: A Versatile Tool to Covalent Organic Frameworks with Tunable Stacking Mode - Hutsch, S.; Leonard, A.; Grätz, S.; Höfler, M. V.; Gutmann, Torsten; Borchardt, L. (Angewandte Chemie-International Edition)
We introduce the first mechanochemical cyclotrimerization of nitriles, a facile strategy for synthesizing triazine-containing molecules and materials, overcoming challenges related to carbonization and solubility. Conducting this solid-state approach in a mixer ball mill with 4-Methylbenzonitrile, we synthesize Tris(4-methylphenyl)-1,3,5-triazine quantitatively in as little as 90 minutes. Just as fast, this mechanochemical method facilitates the synthesis of the covalent triazine framework CTF-1 using 1,4 Dicyanobenzene. Material characterization confirms its porous (650 m2 g-1) and crystalline nature. Adjusting the induced mechanical energy allows control over the obtained stacking conformation of the resulting CTFs - from a staggered AB arrangement to an eclipsed AA stacking conformation. Finally, a substrate scope demonstrates the versatility of this approach, successfully yielding various CTFs. This work presents, for the first time, the mechanochemical cyclotrimerization of nitriles. Utilizing Trifluoromethanesulfonic acid and a ball mill, both small molecules and large organic frameworks could be obtained. Screening the reaction of 1,4-Dicyanobenzene by various parameters, such as reaction time, frequency, or temperature, significant impacts on the porosity of the polymer and its crystallinity were revealed. image

Densities, Viscosities, and Self-Diffusion Coefficients of Octan-1-ol and Related Ether-Alcohols - Hoffmann, Markus M.; Gonzalez, Anthony A.; Huynh, Mandy T.; Miller, Kashane K.; Gutmann, Torsten; Buntkowsky, Gerd (Journal of Chemical & Engineering Data)
Density, viscosity, and self-diffusion coefficients are reported for octan-1-ol and the related ether-alcohols 2-pentoxy-ethan-1-ol, 3-butoxypropan-1-ol, 4-propoxybutan-1-ol, 5-ethoxypentan-1-ol, and 6-methoxyhexan-1-ol covering temperature ranges from 298.15 to 359.15 K. These new data reveal structure–property relationships affected by the presence and the position of the ether moiety in the molecular structure of the ether-alcohols. Compared to octan-1-ol, the presence of the ether moiety causes an increase in intermolecular hydrogen bonding interactions, resulting in higher densities. The increase in density is less pronounced for those ether-octanols that engage in intramolecular hydrogen bonding. As for the effects of the ether moiety on the dynamics, these are generally faster for the ether-alcohols compared to octan-1-ol, suggesting that hydrogen bonding between ether oxygen and hydroxy hydrogen is weaker compared to hydrogen bonding between two hydroxy groups. The activation energies obtained from an Arrhenius analysis are higher for translational motion than for momentum transfer for all alcohols. There are additional finer details across the ether alcohols for these activation barriers. These differences cancel out for the mathematical product of self-diffusion coefficient and viscosity (Dη). The effect of water impurities on the studied properties was also investigated and found to lead to small increases in densities for all alcohols. Viscosities decrease for octan-1-ol and 2-pentoxyethan-1-ol but increase for the other ether-alcohols that can engage in intramolecular hydrogen bonding. Density, viscosity, and self-diffusion coefficients are reported for octan-1-ol and the related ether-alcohols 2-pentoxy-ethan-1-ol, 3-butoxypropan-1-ol, 4-propoxybutan-1-ol, 5-ethoxypentan-1-ol, and 6-methoxyhexan-1-ol covering temperature ranges from 298.15 to 359.15 K. These new data reveal structure–property relationships affected by the presence and the position of the ether moiety in the molecular structure of the ether-alcohols. Compared to octan-1-ol, the presence of the ether moiety causes an increase in intermolecular hydrogen bonding interactions, resulting in higher densities. The increase in density is less pronounced for those ether-octanols that engage in intramolecular hydrogen bonding. As for the effects of the ether moiety on the dynamics, these are generally faster for the ether-alcohols compared to octan-1-ol, suggesting that hydrogen bonding between ether oxygen and hydroxy hydrogen is weaker compared to hydrogen bonding between two hydroxy groups. The activation energies obtained from an Arrhenius analysis are higher for translational motion than for momentum transfer for all alcohols. There are additional finer details across the ether alcohols for these activation barriers. These differences cancel out for the mathematical product of self-diffusion coefficient and viscosity (Dη). The effect of water impurities on the studied properties was also investigated and found to lead to small increases in densities for all alcohols. Viscosities decrease for octan-1-ol and 2-pentoxyethan-1-ol but increase for the other ether-alcohols that can engage in intramolecular hydrogen bonding.

DNP enhanced solid-state NMR – A powerful tool to address the surface functionalization of cellulose/paper derived materials - Höfler, Mark V.; Lins, Jonas; Seelinger, David; Pachernegg, Lukas; Schäfer, Timmy; Spirk, Stefan; Biesalski, Markus; Gutmann, Torsten (Journal of Magnetic Resonance Open)
This concept summarizes recent advances in development and application of DNP enhanced multinuclear solid-state NMR to study the molecular structure and surface functionalization of cellulose and paper-based materials. Moreover, a novel application is presented where DNP enhanced 13C and 15N solid-state NMR is used to identify structure moieties formed by cross-linking of hydroxypropyl cellulose. Given these two aspects of this concept-type of article, we thus combine both, a review on recent findings already published and unpublished recent data that complement the existing knowledge in the field of characterization of functional lignocellulosic materials by DNP enhanced solid-state NMR.
Keywords: solid-state nmr; dynamic nuclear polarization; Hydroxypropyl cellulose; Selective enhancement; Spin labelling

Biradicals based on PROXYL containing building blocks for efficient dynamic nuclear polarization in biotolerant media - Herr, Kevin; Höfler, Mark V.; Heise, Henrike; Aussenac, Fabien; Kornemann, Felix; Rosenberger, David; Brodrecht, Martin; Oliveira, Marcos; Buntkowsky, Gerd; Gutmann, Torsten (Journal of Magnetic Resonance Open)
A versatile strategy for synthesizing tailored peptide based biradicals is presented. By labeling the protected amino acid hydroxyproline with PROXYL via the OH functionality and using this building block in solid phase peptide synthesis (SPPS), the obtained peptides become polarization agents for DNP enhanced solid-state NMR in biotolerant media. To analyze the effect of the radical position on the enhancement factor, three different biradicals are synthesized. The PROXYL spin-label is inserted in a collagen inspired artificial peptide sequence by binding through the OH group of the hydroxyproline moieties at specific position in the chain. This labeling strategy is universally applicable for any hydroxyproline position in a peptide sequence since solid-phase peptide synthesis is used to insert the building block. High performance liquid chromatography (HPLC) and mass spectrometry (MS) analyses show the successful introduction of the spin label in the peptide chain and electron paramagnetic resonance (EPR) spectroscopy confirms its activity. Dynamic nuclear polarization (DNP) enhanced solid-state nuclear magnetic resonance (NMR) experiments performed on frozen aqueous glycerol-d8 solutions containing these peptide radicals show significantly higher enhancement factors of up to 45 in 1H→13C cross polarization magic angle spinning (CP MAS) experiments compared to an analogous mono-radical peptide including this building block (ε ≈ 14). Compared to commercial biradicals such as AMUPol for which enhancement factors {>} 100 have been obtained in the past and which have been optimized in their structure, the obtained enhancement up to 45 for our biradicals presents a significant progress in radical design.
Keywords: solid-state nmr; dynamic nuclear polarization; peptides; Biradicals; Spin labeling